EVA as a Financial Performance Indicator: A Case Study of Two Islamic Rural Banks in Bengkulu - Zahra, Naurah; Isnaini, Desi; Liza, Citra (Fakultas Ekonomi dan Bisnis Islam _ IAIN Sultan Amai Gorontalo, 2025)
This study analyzes the financial performance of BPRS Fadhilah and BPRS Maslahat Dana Syariah Nusantara in Bengkulu City using the Economic Value Added (EVA) method. EVA is selected as a performance indicator because it measures the economic value generated by a company after deducting the cost of capital, providing a clearer picture of value creation for investors and shareholders. This study employs a descriptive quantitative approach, using secondary data obtained from the official financial reports of each bank for the 2023 period. In Indonesia, Islamic banks are classified into three categories: Islamic commercial banks, Islamic business units, and Sharia Rural Credit Banks (BPRS). BPRS primarily focus on providing financing to micro and small enterprises, rather than offering standard payment services. The results show that BPRS Fadhilah recorded a negative EVA, indicating a failure to generate economic value for its investors. Conversely, BPRS Maslahat Dana Syariah Nusantara reported a positive EVA, demonstrating its ability to deliver added value and manage capital effectively. These findings highlight the importance of sound capital management and profitability in enhancing the financial performance of Islamic rural banks.